2007
DOI: 10.1016/j.schres.2006.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in cue detection and intention retrieval underlie prospective memory impairment in schizophrenia

Abstract: Emerging evidence indicates that individuals with schizophrenia (SCZ) may exhibit deficits in prospective memory (ProM), a dissociable and ecologically important aspect of episodic memory entailing the formation, maintenance, and execution of future intentions. The present study aimed to elucidate the component processes of ProM impairment in 41 individuals with SCZ relative to 41 demographically similar healthy comparison (HC) participants. Results revealed that the SCZ group performed worse than HCs on overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
74
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 27 publications
4
74
2
Order By: Relevance
“…In line with previous research (e.g., Kumar et al, 2005;Shum et al, 2004;Woods et al, 2007), participants with schizophrenia demonstrated reduced PM performance in comparison to controls. The core finding of the present study is that in both RM load conditions, people with schizophrenia made significantly fewer PM responses than did controls.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In line with previous research (e.g., Kumar et al, 2005;Shum et al, 2004;Woods et al, 2007), participants with schizophrenia demonstrated reduced PM performance in comparison to controls. The core finding of the present study is that in both RM load conditions, people with schizophrenia made significantly fewer PM responses than did controls.…”
Section: Discussionsupporting
confidence: 91%
“…Further, parallel to the increasing Downloaded by [Temple University Libraries] at 20:40 04 January 2015 demands on executive functions in these tasks, group differences increased from the activity-based over the event-based to the time-based task. However, in contrast with Shum et al's (2004) findings, Woods et al (2007) observed an overall PM deficit in schizophrenia with equivalent impairments in time-and event-based PM. Individuals with schizophrenia were impaired in cue detection and self-directed intention retrieval.…”
contrasting
confidence: 88%
See 2 more Smart Citations
“…Note that, there were insufficient numbers of Place Losing Omissions (n = 0) and Random Errors (n = 2) to permit meaningful analyses. Finally, a 3-choice recognition trial was administered following the completion of all eight ProM tasks (range = 0-8), from which a Retrieval Index was derived by subtracting free recall accuracy (range = 0-8) such that higher scores indicate a greater retrieval deficit (see Woods et al, 2007b).Self-reported ProM was assessed with the Prospective and Retrospective Memory Questionnaire (PRMQ; Smith, Della Sala, Logie, & Maylor, 2000), which is a 16-item questionnaire on which perceived memory difficulties are rated on a 5-point Likert-type scale that ranges from 1 ("never") to 5 ("very often" , 1997). The delayed free recall scores from these three measures were converted to sample-based z-scores (n = 66) and then averaged to create a composite measure of RetM.…”
mentioning
confidence: 99%